Opportunities and Challenges Digital Tax in Indonesia - Notika Rahmi; Pebriana Arimbhi; Winda Wulandari; Alief Ramdan; Idar Rachmatulloh (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
The number of transactions carried out online during this pandemic has become an opportunity/potential and challenge for the Government in terms of state revenues, namely from the tax sector, especially income tax (PPh) and Value Added Tax (VAT) revenues. The imposition of a digital tax will provide a sense of justice because foreign companies will get the same treatment as domestic companies that do have an obligation to pay taxes. This is also to create a level of playing field and healthy competition. The purpose of this study is to analyze the opportunities and challenges of digital taxes in Indonesia. The research method used is qualitative. The results of the study show that the application of digital taxes in Indonesia has a very large opportunity so that the government has issued various regulations to achieve the tax target. In terms of optimizing tax revenue, the Government expands Tax Objects and Subjects for VAT and PPh and Increases Taxpayer Compliance. However, it should be noted that the challenges that will be faced are the preparation of skilled and professional human resources, increasing collaboration with digital payment platforms so that they are connected to tax data and the availability of qualified internet access.